Measuring Skills Demanded by Employers : Skills Toward Employment and Productivity (STEP) - Sanchez Puerta, Maria Laura; Rizvi, Anam (World Bank, Washington, DC, 2018)
Economic growth depends on skills being put to productive use. In recent years, research on labor outcomes and education shows that there is a substantial mismatch between the supply and demand for skills around the world (Cappelli, 2014: McIntosh and Vignoles, 2001). This mismatch affects more than just wages or individual job satisfaction. Skills mismatches have an impact on productivity and growth at both the firm level and the macro-economic level (Quintini, 2014). Reports show that firms around the world consider skills challenges to be an impediment to the operation and development of their business. A cause for further concern is that this constraint seems to be disproportionately affecting the more dynamic and innovative employers, signifying a potentially negative impact on job creation and technological progress (World Bank, 2012).